Access, Deconstructed: Metajournalistic Discourse and Photojournalism's Shift Away From Geophysical Access. (April 2018) - Ferrucci, Patrick; Taylor, Ross
This study examines metajournalistic discourse published surrounding the intersection of photojournalism and access. Researchers conducted a textual analysis of metajournalistic discourse published in articles by The Image, Deconstructed, the photojournalism industry blog, from 2011 to 2017 ( N =70). Findings suggest that photojournalists define access differently than scholars. They obtain access through purposeful body language and verbal communication, clarity of intent, and persistence. These findings are interpreted through the lens of the theory of metajournalistic discourse.